Distribution Channel Reengineering: A Case Study - Maslarić, Marinko; Groznik, Aleš; Brnjac, Nikolina (Promet - Traffic&Transportation, 2012)
For the last few decades there has been growing interest in making more integrated business decisions across larger segments of the logistic and distribution networks. Modern information technology is allowing this idea to be implemented, but there is need to develop a way of effective use of information technologies that support this business direction. In this paper a methodology to assist distribution networks reengineering with the aim of integrating logistic processes within the distribution supply chain has been promoted. The emphasis of methodology is on the business processes modelling and reengineering in the distribution network. Finally, this paper presents an oil company case study to illustrate how the methodology can be applied in practice. Keywords: distribution process, business process modelling, reengineering, information sharing, logistics